Hydrolysis catalyst for removing organic sulfur as well as preparation method and application of hydrolysis catalyst
By supporting the composite active components of alkali metal oxide and titanium oxide/molybdenum oxide on the aluminum-based oxide support, a hydrolysis catalyst with high efficiency anti-sulfur poisoning ability is solved, and the hydrolysis catalyst in the prior art is solved. The problem of insufficient anti-sulfur poisoning ability at low temperatures has achieved efficient and environmentally friendly organic sulfur removal and low-cost production.
Patent Information
- Application Number
- CN202310702695.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-20
AI Technical Summary
The existing hydrolysis catalysts have insufficient anti-sulfur poisoning ability at medium and low temperatures, and the preparation process is complicated and environmentally friendly, resulting in limited industrial applications.
By supporting alkali metal oxides and titanium oxides/molybdenum oxides as composite active components on the aluminum-based oxide support, a hydrolysis catalyst with anti-sulfur poisoning ability is formed. The preparation method of inorganic solvents is used to avoid organic The use of solvents reduces costs and equipment requirements.
It has achieved efficient removal of organic sulfur at medium and low temperatures, and its anti-sulfur poisoning ability reaches more than 99%, reducing production costs, and is environmentally friendly and has significant economic and social benefits.
Smart Images

Figure CN119158564A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a hydrolysis catalyst for removing organic sulfur, a preparation method and an application thereof. Background Art
[0002] Organic sulfur, represented by carbonyl sulfide (COS), is widely present in coke oven gas, blast furnace gas and fuel gas. The presence of organic sulfur will not only corrode pipeline equipment, but also cause sulfur poisoning to the catalyst in the downstream process flow, making it inactive. In addition, the combustion of high-sulfur fuel gas will cause serious damage to the environment. With the gradual strengthening of environmental protection policies, the effective use of high-sulfur combustible gas will be restricted. Therefore, the precise removal of COS is of great significance.
[0003] COS removal methods are mainly divided into two categories: dry desulfurization and wet desulfurization. At present, the process technology of wet desulfurization is relatively mature, but there are still problems such as large equipment, large resistance in the mass transfer process, low removal efficiency, and high industrial technology cost. Compared with wet desulfurization, dry desulfurization has the advantages of high conversion rate, simple operation, and less side reactions. In addition, when the sulfur content in the atmosphere is low, only the dry method can achieve the final removal effect, so this method has been widely used. Dry desulfurization is mainly divided into adsorption method and catalytic conversion method, among which the catalytic conversion method includes hydrogenation conversion catalytic method, catalytic hydrolysis method and catalytic oxidation method. The water vapor required for the catalytic hydrolysis process generally already exists in the raw gas, no additional addition is required, and the reaction does not require an external hydrogen source. Compared with the oxidation conversion method and the hydrogenation conversion method, the catalytic hydrolysis method has the advantages of saving energy consumption, low temperature, no consumption of raw materials, and few side reactions. Therefore, the hydrolysis conversion method has a wider application and has received a lot of attention.
[0004] The most widely used hydrolysis catalyst is Al 2 O 3 As a carrier, by loading other active components or additives, the catalytic activity is improved and the COS hydrolysis conversion rate is increased. 2 O 3 The active components loaded on the surface mainly include alkali metals, alkaline earth metals and transition metal oxides. For example, patent CN106861665A discloses an Al 2 O 3 A method for preparing a carbonyl sulfide hydrolysis catalyst. Although the aluminum oxide carbonyl sulfide catalyst obtained by the method has a good desulfurization effect, the preparation method is not only cumbersome, but also uses a large amount of organic solvents, which will cause environmental pollution and is not conducive to industrial application.
[0005] In addition, during the use of COS hydrolysis catalytic technology, there is a problem of catalyst sulfur poisoning. Experimental studies have shown that the main causes of COS hydrolysis agent poisoning are: 1. At low temperatures, sulfur deposition is the main cause of hydrolysis agent poisoning; 2. 2 S and O 2 When acting at the same time, the hydrolyzing agent will be poisoned; 3. Oxygen concentration has a significant effect on catalyst poisoning. The higher the oxygen concentration, the higher the catalyst deactivation rate. Therefore, improving the anti-sulfur poisoning performance of COS hydrolyzing agent is a key goal of COS catalyst preparation and application process. For example, the CN1844326A invention patent of Hubei Institute of Chemistry is to remove the oxygen component in the gas by loading modified activated carbon during the removal process, eliminating O in the gas from the perspective of process improvement. 2 The effect of subsequent COS hydrolysis agent poisoning is reduced, and the anti-poisoning ability of COS hydrolysis catalyst is finally improved. However, the invention has the problems of complex process, high equipment requirements and high cost.
[0006] Therefore, it is of great significance to study a hydrolysis catalyst that can resist sulfur poisoning at medium and low temperatures while reducing costs and being environmentally friendly. Summary of the invention
[0007] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a hydrolysis catalyst for removing organic sulfur, and a preparation method and application thereof. The present invention obtains a hydrolysis catalyst that has the ability to resist sulfur poisoning at medium and low temperatures by adding a first active component and a second active component. The first active component changes the alkalinity of the hydrolysis catalyst. The synergistic cooperation with the second active component not only improves the ability of the hydrolysis catalyst to resist sulfur poisoning, but also realizes the medium and low temperature removal of organic sulfur in organic sulfur-containing gas. The hydrolysis effect of the organic sulfur can reach more than 99%. In addition, the hydrolysis catalyst has a low manufacturing cost and is environmentally friendly, so it has a strong practical application value, and significant economic and social benefits.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a hydrolysis catalyst for removing organic sulfur, the hydrolysis catalyst comprising a carrier and a composite active component supported on the carrier;
[0010] The support comprises at least one aluminum-based oxide;
[0011] The composite active component includes a first active component and a second active component;
[0012] The first active component includes an alkali metal oxide, and the second active component includes a titanium-based oxide and / or a molybdenum-based oxide.
[0013] The present invention obtains a hydrolysis catalyst having sulfur poisoning resistance at medium and low temperatures by adding a first active component and a second active component. The first active component changes the alkalinity of the hydrolysis catalyst. Under the synergistic effect of the first active component and the second active component, not only the sulfur poisoning resistance of the hydrolysis catalyst is improved, but also the organic sulfur in the organic sulfur-containing gas is removed at medium and low temperatures. The hydrolysis effect of the organic sulfur can reach more than 99%. In addition, the hydrolysis catalyst has low manufacturing cost and is environmentally friendly, so it has strong practical application value and significant economic and social benefits.
[0014] As a preferred technical solution of the present invention, the second active component is a composition of titanium-based oxide and molybdenum-based oxide.
[0015] In the present invention, adding titanium-based oxide and molybdenum-based oxide as the second active component can modify the hydrolysis catalyst, effectively improve the anti-sulfur poisoning ability of the hydrolysis catalyst, and synergize with the first active component, so that the hydrolysis catalyst can maintain a high hydrolysis conversion efficiency while improving the anti-sulfur poisoning ability in oxygen-containing combustible gas and extending the service life.
[0016] Preferably, in the alkali metal oxide, the alkali metal includes any one of Na, K or Cs or a combination of at least two thereof, preferably a combination of Na and K.
[0017] As a preferred technical solution of the present invention, based on the mass of the hydrolysis catalyst, the mass percentage of the composite active component is 15-20wt.%, for example, it can be 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, etc.
[0018] In the present invention, if the mass percentage of the composite active component is too small, that is, the amount of the composite active component is too little, the hydrolysis conversion efficiency is low and cannot meet the use requirements; if the mass percentage of the composite active component is too large, that is, the amount of the composite active component is too much, the adsorption of inorganic sulfur generated after hydrolysis is enhanced, and desorption release is not utilized, resulting in sulfur deposition on the catalyst surface, thereby causing sulfur poisoning of the catalyst.
[0019] Preferably, based on the mass of the hydrolysis catalyst, the mass percentage of the carrier is 80-85wt.%, for example, 80wt.%, 81wt.%, 82wt.%, 83wt.%, 84wt.% or 85wt.%, etc.
[0020] Preferably, the mass ratio of the first active component to the second active component is (5-10):(7-15), wherein the selection range of the first active component "5-10" can be, for example, 5, 6, 7, 8, 9 or 10, and the selection range of the second active component "7-15" can be, for example, 7, 8, 9, 10, 11, 12, 13, 14 or 15, etc.
[0021] In the present invention, if the mass ratio of the first active component to the second active component is too small, that is, the amount of the second active component is too much, the catalytic hydrolysis conversion efficiency is reduced; if the mass ratio of the first active component to the second active component is too large, that is, the amount of the second active component is too small, the anti-sulfur poisoning effect is weakened and the service life is shortened.
[0022] Preferably, in the second active component, the mass ratio of titanium-based oxide to molybdenum-based oxide is (5-10):(2-5), wherein the selection range of titanium-based oxide is "5-10", for example, it can be 5, 6, 7, 8, 9 or 10, etc., and the selection range of molybdenum-based oxide is "2-5", for example, it can be 2, 3, 4 or 5, etc.
[0023] As a preferred technical solution of the present invention, the hydrolysis catalyst has a mesoporous channel structure, and the mesopore diameter of the mesoporous channel structure is 2-20nm, for example, it can be 2nm, 4nm, 10nm or 20nm.
[0024] The hydrolysis catalyst prepared by the invention has a mesoporous channel structure and can well adsorb organic sulfur.
[0025] Preferably, the BET specific surface area of the hydrolysis catalyst is 150-300 m 2 / g, for example, it can be 150m 2 / g, 200m 2 / g, 250m 2 / g or 300m 2 / g, etc.
[0026] In the present invention, N 2 The physical adsorption method can detect the BET specific surface area of the hydrolysis catalyst.
[0027] In a second aspect, the present invention provides a method for preparing the hydrolysis catalyst as described in the first aspect, the preparation method comprising the following steps:
[0028] The carrier precursor, the composite active component precursor and the solvent are mixed, reacted and calcined to obtain the hydrolysis catalyst;
[0029] The composite active component precursor includes a first active component precursor and a second active component precursor, the first active component precursor includes an alkali metal element, and the second active component precursor includes a titanium source and / or a molybdenum source.
[0030] The preparation method provided by the present invention overcomes the problem of complicated processes in the prior art, and does not require the use of organic solvents and acidic solvents in the preparation process, has low equipment requirements, low cost, and does not cause pollution to the environment. It has strong practical application value and significant economic and social benefits.
[0031] As a preferred technical solution of the present invention, the carrier precursor includes any one of pseudo-boehmite, γ-aluminum oxide or aluminum oxide hydroxide, or a combination of at least two thereof.
[0032] It should be noted that pseudo-boehmite is also known as monohydrated aluminum oxide and pseudo-boehmite, and its general chemical formula is AlOOH·nH 2 O, n = 0.08-0.62, is a type of transitional product from disorder to order, weakly crystalline to crystalline with uncertain composition and incomplete crystallization. The crystal structure is completely similar to that of boehmite.
[0033] Preferably, the first active component precursor comprises an alkali metal salt and / or an alkali metal hydroxide, preferably an alkali metal salt and an alkali metal hydroxide.
[0034] Preferably, the alkali metal salt comprises a carbonate.
[0035] Preferably, the titanium source includes any one of titanium dioxide, titanium nitrate or titanate, or a combination of at least two thereof.
[0036] Preferably, the molybdenum source comprises ammonium molybdate and / or molybdenum oxide.
[0037] Preferably, the mass ratio of the carrier precursor to the composite active component precursor is (6-10):(1-3), wherein the mass selection range of the carrier precursor "6-10" can be, for example, 6, 7, 8, 9 or 10, and the mass selection range of the composite active component precursor "1-3" can be, for example, 1, 1.5, 2, 2.5 or 3.
[0038] Preferably, the solvent comprises water.
[0039] The present invention uses only inorganic solvents, and does not need to use organic solvents or acidic solvents, thus overcoming the defect of the prior art that organic solvents or acidic solvents are used when preparing hydrolysis catalysts.
[0040] As a preferred technical solution of the present invention, the mixing process is accompanied by stirring.
[0041] Preferably, the specific manner of mixing includes:
[0042] Dispersing the first active component precursor and the molybdenum source in a solvent to obtain a dispersion, and adding the carrier precursor and the titanium source into the dispersion for blending; or,
[0043] The first active component precursor and the titanium source are dispersed in a solvent to obtain a dispersion, and the carrier precursor and the molybdenum source are added into the dispersion for blending.
[0044] The present invention adopts the above mixing method, so that the carrier and the active component can be fully dispersed, and the active component is evenly dispersed on the surface of the carrier. In addition, the preparation process is relatively simple and easy to mass produce.
[0045] Preferably, the reaction temperature is room temperature.
[0046] In the present invention, room temperature refers to 25±5°C, for example, it may be 20°C, 22°C, 24°C, 26°C, 28°C or 30°C.
[0047] Preferably, the reaction time is 6-12 h, for example, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h.
[0048] Preferably, the calcination temperature is 350-650°C, for example, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C, etc., preferably 500-600°C.
[0049] In the present invention, if the roasting temperature is too low, some substances cannot be completely converted, and the catalytic hydrolysis conversion efficiency is low; if the roasting temperature is too high, other substances will be generated, the catalytic hydrolysis conversion efficiency will be low, and the production cost will increase.
[0050] Preferably, the calcination time is 3-5 h, for example, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, etc., preferably 3.5-4.5 h.
[0051] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0052] (1) stirring and dispersing an alkali metal salt, an alkali metal hydroxide and a molybdenum source in a solvent to obtain a dispersion, adding a carrier precursor and a titanium source to the dispersion, stirring and mixing, reacting at room temperature for 6-12 hours, evaporating the solvent at 70-90° C. after the reaction, and then drying at 100-120° C. for 3-6 hours;
[0053] (2) calcining the dried product in an air atmosphere at a temperature of 350-650° C. for 3-5 hours to obtain the hydrolysis catalyst;
[0054] Wherein, the heating rate of the calcination temperature is 3-5°C / min.
[0055] In a third aspect, the present invention provides a use of the hydrolysis catalyst as described in the first aspect, wherein the hydrolysis catalyst is used for removing organic sulfur from oxygen-containing combustible gas at medium and low temperatures.
[0056] The present invention does not specifically limit the type of oxygen-containing combustible gas. For example, it may be blast furnace gas, coke oven gas or fuel gas.
[0057] Preferably, the type of organic sulfur includes carbonyl sulfide.
[0058] Preferably, the oxygen content of the oxygen-containing combustible gas is 0-3%, excluding 0, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5% or 3%, etc.
[0059] Preferably, the medium-low temperature is 80-160°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C.
[0060] The hydrolysis catalyst prepared by the present invention can remove organic sulfur at medium and low temperatures, which can reduce energy consumption for enterprises during the desulfurization process. Moreover, for oxygen-containing combustible gases, the use of medium and low temperature desulfurization is beneficial to improving safety.
[0061] As a preferred technical solution of the present invention, during the process of removing organic sulfur with the hydrolysis catalyst, the air velocity is 6000-1000h -1 , for example, it can be 6000h -1 、7000h -1 、8000h -1 , 9000h -1 or 10000h -1 wait.
[0062] Preferably, the concentration of organic sulfur in the oxygen-containing combustible gas is 5-2000 mg / m 3 For example, 5 mg / m 3 , 10mg / m 3 , 50mg / m 3 , 100mg / m 3 , 500mg / m 3 , 1000mg / m 3 , 1500mg / m 3 or 2000 mg / m 3 wait.
[0063] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] (1) The present invention obtains a hydrolysis catalyst that is resistant to sulfur poisoning at medium and low temperatures by adding a first active component and a second active component. The first active component changes the alkalinity of the hydrolysis catalyst. The synergistic cooperation with the second active component not only improves the ability of the hydrolysis catalyst to resist sulfur poisoning, but also achieves medium and low temperature removal of organic sulfur in organic sulfur-containing gas. The hydrolysis effect of the organic sulfur can reach more than 99%.
[0066] (2) The preparation method provided by the present invention overcomes the problem of complicated process in the prior art, and no organic solvent or acidic solvent is required in the preparation process, which has low requirements on equipment, low cost, and will not cause pollution to the environment.
[0067] (3) The hydrolysis catalyst provided by the present invention has strong practical application value and significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is the XRD diffraction pattern of the hydrolysis catalyst prepared in Example 1 of the present invention.
[0069] Figure 2 This is the pore size distribution diagram of the hydrolysis catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0071] Example 1
[0072] This embodiment provides a hydrolysis catalyst for removing organic sulfur, the hydrolysis catalyst comprising a carrier and a composite active component supported on the carrier, the carrier being a mixture of γ-aluminum trioxide and aluminum oxyhydroxide, the composite active component comprising a first active component and a second active component, the first active component comprising potassium oxide and sodium oxide, the second active component comprising titanium dioxide and molybdenum dioxide;
[0073] Wherein, based on the mass of the hydrolysis catalyst, the mass percentage of the carrier is 80wt.%, the mass percentage of the composite active component is 20wt.%, the mass ratio of the first active component to the second active component is 10:15, the mass ratio of titanium dioxide to molybdenum dioxide is 8:3, the hydrolysis catalyst has a mesoporous channel structure, the mesopore diameter of the mesoporous channel structure is 2-20nm, and the BET specific surface area of the hydrolysis catalyst is 200m 2 / g.
[0074] This embodiment also provides a method for preparing the above hydrolysis catalyst, the preparation method comprising the following steps:
[0075] (1) 1 g of potassium carbonate, 0.035 g of sodium hydroxide and 0.5 g of ammonium molybdate are stirred and dispersed in water to form a dispersion, 10 g of pseudo-boehmite and 1 g of titanium dioxide are added to the dispersion under stirring conditions, mixed, stirred at room temperature of 25° C. for 12 h to react, water is evaporated at 80° C. after the reaction, and the obtained product is placed in an oven at 105° C. for drying for 3 h;
[0076] Wherein, the mass ratio of the carrier precursor (i.e., pseudo-boehmite) to the composite active component precursor (i.e., including potassium carbonate, sodium hydroxide, ammonium molybdate and ammonium molybdate) is 10:2.535;
[0077] (2) The dried sample is placed in a crucible, calcined in a muffle furnace at 550° C. in an air atmosphere for 4 h, and then mechanically pressed into tablets, and sieved through 30-50 meshes to obtain the hydrolysis catalyst.
[0078] The hydrolysis catalyst prepared in Example 1 was subjected to XRD test and physical adsorption test.
[0079] XRD test uses D8 ADVANCE X-ray diffractometer. The incident X-ray is Kα ray generated by rotating Cu with a wavelength of The X-ray spectrum was obtained by continuous scanning with a scanning speed of 10° / min and a scanning range of 2θ=0-90°.
[0080] The results of XRD test are as follows Figure 1 As shown in the figure, it can be seen that the hydrolysis catalyst prepared in this embodiment is γ-Al 2 O 3 In the mixture of aluminum oxyhydroxide and aluminum oxyhydroxide, no diffraction peaks of other metal oxides were observed, indicating that the first active component and the second active component were uniformly dispersed on the aluminum-based carrier.
[0081] Physical adsorption was performed using the ASAP 2020M physical adsorption instrument from Micrometric, USA, to analyze physical structural parameters such as pore size. The specific test method was as follows: 0.1 g of the sieved catalyst sample was weighed and degassed at 160 °C under high vacuum for 12 h. 2 As adsorbent, the low temperature N 2 The adsorption-desorption isotherm was used to obtain the catalyst pore size distribution.
[0082] The results of the physical adsorption test are as follows Figure 2 As shown in the figure, it can be seen that the hydrolysis catalyst prepared in this embodiment has mesopores. The mesoporous material has a relatively large specific surface area, a relatively large pore size and a regular pore structure, and can adsorb organic sulfur very well.
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (2) is adjusted to 350°C.
[0085] The rest of the preparation methods and parameters were the same as those in Example 1.
[0086] Example 3
[0087] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (2) is adjusted to 450°C.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Example 4
[0090] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (2) is adjusted to 650°C.
[0091] The rest of the preparation methods and parameters were the same as those in Example 1.
[0092] Example 5
[0093] The difference between this embodiment and embodiment 1 is that in step (1), ammonium molybdate is not added, but potassium carbonate and sodium hydroxide are directly dispersed in water.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Example 6
[0096] The difference between this embodiment and embodiment 1 is that titanium dioxide is not added in step (1), but pseudo-boehmite is directly added to the dispersion for mixing.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Example 7
[0099] The difference between this embodiment and embodiment 1 is that in step (1), no sodium hydroxide is added, but potassium carbonate and ammonium molybdate are dispersed in water.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 8
[0102] The difference between this embodiment and embodiment 1 is that potassium carbonate is not added in step (1), but sodium hydroxide and ammonium molybdate are dispersed in water.
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 9
[0105] The difference between this embodiment and embodiment 1 is that in step (1), potassium carbonate, sodium hydroxide, ammonium molybdate, pseudo-boehmite and titanium dioxide are first ground and mixed, and then dispersed in water.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 10
[0108] This embodiment provides a hydrolysis catalyst for removing organic sulfur, the hydrolysis catalyst comprising a carrier and a composite active component supported on the carrier, the carrier being γ-Al 2 O 3 and a mixture of aluminum oxyhydroxide, the composite active component comprising a first active component and a second active component, the first active component comprising potassium oxide and sodium oxide, the second active component comprising titanium dioxide and molybdenum dioxide;
[0109] Wherein, based on the mass of the hydrolysis catalyst, the mass percentage of the carrier is 82wt.%, the mass percentage of the composite active component is 18wt.%, the mass ratio of the first active component to the second active component is 10:15, the mass ratio of titanium dioxide to molybdenum dioxide is 10:5, the mesopore diameter of the mesoporous channel structure is 2-20nm, and the BET specific surface area of the hydrolysis catalyst is 150m 2 / g.
[0110] This embodiment also provides a method for preparing the above hydrolysis catalyst, the preparation method comprising the following steps:
[0111] (1) 0.9 g of potassium carbonate, 0.0315 g of sodium hydroxide and 0.45 g of ammonium molybdate were stirred and dispersed in water to form a dispersion, 10.25 g of pseudo-boehmite and 0.9 g of titanium dioxide were added to the dispersion under stirring conditions and mixed, and stirred at room temperature of 25° C. for 9 h to react, and after the reaction, water was evaporated at 70° C., and then the obtained product was placed in an oven at 110° C. for drying for 6 h;
[0112] The mass ratio of the carrier precursor (i.e., pseudo-boehmite) to the composite active component precursor (i.e., including potassium carbonate, sodium hydroxide, ammonium molybdate and titanium dioxide) is 10.25:2.28;
[0113] (2) The dried sample is placed in a crucible, calcined in a muffle furnace at 350° C. in an air atmosphere for 5 h, and then mechanically pressed into tablets, and sieved through 30-50 meshes to obtain the hydrolysis catalyst.
[0114] Embodiment 11
[0115] This embodiment provides a hydrolysis catalyst for removing organic sulfur, the hydrolysis catalyst comprising a carrier and a composite active component supported on the carrier, the carrier being γ-Al 2 O 3 and a mixture of aluminum oxyhydroxide, the composite active component comprising a first active component and a second active component, the first active component comprising potassium oxide and sodium oxide, the second active component comprising titanium dioxide and molybdenum dioxide;
[0116] Wherein, based on the mass of the hydrolysis catalyst, the mass percentage of the carrier is 85wt.%, the mass percentage of the composite active component is 15wt.%, the mass ratio of the first active component to the second active component is 8:10, the mass ratio of titanium dioxide to molybdenum dioxide is 8:4, the hydrolysis catalyst has a mesoporous channel structure, the mesopore diameter of the mesoporous channel structure is 2-20nm, and the BET specific surface area of the hydrolysis catalyst is 300m 2 / g.
[0117] This embodiment also provides a method for preparing the above hydrolysis catalyst, the preparation method comprising the following steps:
[0118] (1) 0.75 g of potassium carbonate, 0.02625 g of sodium hydroxide and 0.375 g of ammonium molybdate were stirred and dispersed in water to form a dispersion, 10.625 g of pseudo-boehmite and 0.75 g of titanium dioxide were added to the dispersion under stirring conditions, mixed, stirred at room temperature of 25° C. for 6 h to react, and after the reaction, water was evaporated at 90° C., and then the obtained product was placed in an oven at 120° C. for drying for 4 h;
[0119] The mass ratio of the carrier precursor (i.e., pseudo-boehmite) to the composite active component precursor (i.e., including potassium carbonate, sodium hydroxide, ammonium molybdate and titanium dioxide) is 10.625:1.901;
[0120] (2) The dried sample is placed in a crucible, calcined in a muffle furnace at 650° C. in an air atmosphere for 3 h, and then mechanically pressed into tablets, and sieved through 30-50 meshes to obtain the hydrolysis catalyst.
[0121] Example 12
[0122] The difference between this embodiment and embodiment 1 is that the mass percentage of the composite active component is 10 wt.% by adjusting the amount of the composite active component precursor.
[0123] The rest of the preparation methods and parameters were the same as those in Example 1.
[0124] Example 13
[0125] The difference between this embodiment and embodiment 1 is that the mass percentage of the composite active component is 25 wt.% by adjusting the amount of the composite active component precursor.
[0126] The rest of the preparation methods and parameters were the same as those in Example 1.
[0127] Embodiment 14
[0128] The difference between this embodiment and embodiment 1 is that the mass ratio of the first active component to the second active component in the hydrolysis catalyst is 5:20 by adjusting the dosage of the second active component precursor (including ammonium molybdate and titanium dioxide).
[0129] The rest of the preparation methods and parameters were the same as those in Example 1.
[0130] Embodiment 15
[0131] The difference between this embodiment and embodiment 1 is that the mass ratio of the first active component to the second active component in the hydrolysis catalyst is 10:5 by adjusting the dosage of the second active component precursor (including ammonium molybdate and titanium dioxide).
[0132] The rest of the preparation methods and parameters were the same as those in Example 1.
[0133] Example 16
[0134] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (2) is adjusted to 300°C.
[0135] The rest of the preparation methods and parameters were the same as those in Example 1.
[0136] Embodiment 17
[0137] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (2) is adjusted to 700°C.
[0138] The rest of the preparation methods and parameters were the same as those in Example 1.
[0139] Comparative Example 1
[0140] The difference between this comparative example and Example 1 is that ammonium molybdate and titanium dioxide are not added in step (1), so that the obtained hydrolysis catalyst does not contain the second active component.
[0141] The rest of the preparation methods and parameters were the same as those in Example 1.
[0142] Performance Testing
[0143] The hydrolysis catalysts prepared in Examples 1-17 and Comparative Example 1 were tested, and the activity and stability results were expressed in terms of carbonyl sulfide (COS) conversion. The COS concentrations in the feed gas and the discharge gas were tracked using a gas chromatograph.
[0144] Test process: The activity test of COS catalytic hydrolysis was carried out in a fixed bed quartz reactor. The inner diameter of the reaction tube was 1 cm and the hydrolysis agent loading was 0.5 cm 3 , height is about 0.3cm, particle size is 30-50 mesh, reaction temperature is 80-160℃, heating rate is 3℃ / min. COS concentration in raw gas is 2000mg / m 3 The mixed gas containing hydrogen, methane, carbon monoxide, carbon dioxide and oxygen is the balance gas, the raw gas flow rate is 20mL / min, and the space velocity is 6000h -1 , the water vapor temperature in the reactants is 40°C.
[0145] Test conditions: The test temperature points were spaced 20°C apart, and each sample was sampled and tested after 1h and 20h of reaction.
[0146] The calculation formula of COS conversion rate is:
[0147] COS conversion rate (%) = (COS concentration in feed gas - COS concentration in outlet gas) / COS concentration in feed gas × 100%.
[0148] The test results are shown in Table 1.
[0149] Table 1
[0150]
[0151]
[0152]
[0153] The hydrolysis catalysts prepared in Examples 1-17 and Comparative Example 1 were tested for their ability to resist sulfur poisoning. The test process was the same as above, the reaction temperature was 80°C, and when the hydrolysis conversion efficiency was lower than 80%, it was considered that breakthrough had been achieved and the test was stopped.
[0154] The test results are shown in Table 2.
[0155] Table 2
[0156]
[0157]
[0158] analyze:
[0159] It can be seen from Table 1 and Table 2 that the hydrolysis catalyst provided by the present invention has excellent carbonyl sulfide conversion efficiency, and its hydrolysis effect can reach more than 99%, and the hydrolysis catalyst has excellent sulfur poisoning resistance at 80-160°C.
[0160] It can be seen from the data results of Example 1 and Examples 5-6 that if only titanium dioxide or ammonium molybdate is added, the ability to resist sulfur poisoning is weakened.
[0161] It can be seen from the data results of Example 1 and Examples 7-8 that if only potassium carbonate is used as the first active component, the activity is insufficient, resulting in a poor hydrolysis effect. If only sodium hydroxide is used as the first active component without adding potassium carbonate, the catalytic activity is insufficient, resulting in a serious decrease in the catalytic hydrolysis conversion efficiency and poor resistance to sulfur poisoning.
[0162] It can be seen from the data results of Example 1 and Example 9 that if potassium carbonate, sodium hydroxide, ammonium molybdate, pseudo-boehmite and titanium dioxide are directly ground, mixed and dispersed in water, the activity will only decrease slightly, the hydrolysis effect is better, and the resistance to sulfur poisoning is better.
[0163] It can be seen from the data results of Example 1 and Examples 12-13 that if the mass percentage of the composite active component is too low, the active component is insufficient, resulting in a lower hydrolysis effect; if the mass percentage of the composite active component is too high, the active component is excessive, and its ability to resist sulfur poisoning decreases.
[0164] It can be seen from the data results of Example 1 and Examples 14-15 that if the mass ratio of the first active component to the second active component in the hydrolysis catalyst is too small, the active component is insufficient, thereby reducing its hydrolysis effect; if the mass ratio of the first active component to the second active component in the hydrolysis catalyst is too large, the overall alkalinity of the catalyst is too strong, which is not conducive to the desorption of inorganic sulfur produced by hydrolysis, and its ability to resist sulfur poisoning is weakened.
[0165] It can be seen from the data results of Example 1 and Examples 16-17 that if the roasting temperature is too low, the components cannot be completely converted, so that the hydrolysis effect cannot meet the use requirements and its resistance to sulfur poisoning is not obvious; if the roasting temperature is too high, the active components are converted into other substances, thereby reducing its hydrolysis effect.
[0166] It can be seen from the data results of Example 1 and Comparative Example 1 that if the hydrolysis catalyst does not contain the first active component, the activity is insufficient, resulting in poor hydrolysis effect, failure to meet the use requirements, and poor resistance to sulfur poisoning.
[0167] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A hydrolysis catalyst for removing organic sulfur, characterized in that: The hydrolysis catalyst comprises a carrier and a composite active component supported on the carrier; The support comprises at least one aluminum-based oxide; The composite active component includes a first active component and a second active component; The first active component includes an alkali metal oxide, and the second active component includes a titanium-based oxide and / or a molybdenum-based oxide.
2. The hydrolysis catalyst according to claim 1, characterized in that The second active component is a composition of titanium-based oxide and molybdenum-based oxide; Preferably, in the alkali metal oxide, the alkali metal includes any one of Na, K or Cs or a combination of at least two of them.
3. The hydrolysis catalyst according to claim 1 or 2, characterized in that Based on the mass of the hydrolysis catalyst, the mass percentage of the composite active component is 15-20wt.%; Preferably, based on the mass of the hydrolysis catalyst, the mass percentage of the carrier is 80-85wt.%; Preferably, the mass ratio of the first active component to the second active component is (5-10):(7-15); Preferably, in the second active component, the mass ratio of titanium-based oxide to molybdenum-based oxide is (5-10):(2-5).
4. The hydrolysis catalyst according to any one of claims 1 to 3, characterized in that The hydrolysis catalyst has a mesoporous channel structure, and the mesopore diameter of the mesoporous channel structure is 2-20 nm.
5. A method for preparing a hydrolysis catalyst as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The carrier precursor, the composite active component precursor and the solvent are mixed, reacted and calcined to obtain the hydrolysis catalyst; The composite active component precursor includes a first active component precursor and a second active component precursor, the first active component precursor includes an alkali metal element, and the second active component precursor includes a titanium source and / or a molybdenum source.
6. The preparation method according to claim 5, characterized in that: The carrier precursor includes any one of pseudo-boehmite, γ-aluminum oxide or aluminum oxyhydroxide, or a combination of at least two thereof; Preferably, the first active component precursor comprises an alkali metal salt and / or an alkali metal hydroxide, preferably an alkali metal salt and an alkali metal hydroxide; Preferably, the titanium source includes any one or a combination of at least two of titanium dioxide, titanium nitrate or titanate; Preferably, the molybdenum source comprises ammonium molybdate and / or molybdenum oxide; Preferably, the mass ratio of the carrier precursor to the composite active component precursor is (6-10):(1-3); Preferably, the solvent comprises water.
7. The preparation method according to claim 5 or 6, characterized in that: The mixing process is accompanied by stirring; Preferably, the specific manner of mixing includes: Dispersing the first active component precursor and the molybdenum source in a solvent to obtain a dispersion, and adding the carrier precursor and the titanium source into the dispersion for blending; or, Dispersing a first active component precursor and a titanium source in a solvent to obtain a dispersion, and adding a carrier precursor and a molybdenum source into the dispersion for blending; Preferably, the reaction temperature is room temperature; Preferably, the reaction time is 6-12h; Preferably, the calcination temperature is 350-650°C, preferably 500-600°C; Preferably, the calcination time is 3-5 h, preferably 3.5-4.5 h.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method comprises the following steps: (1) stirring and dispersing an alkali metal salt, an alkali metal hydroxide and a molybdenum source in a solvent to obtain a dispersion, adding a carrier precursor and a titanium source to the dispersion, stirring and mixing, reacting at room temperature for 6-12 hours, evaporating the solvent at 70-90° C. after the reaction, and then drying at 100-120° C. for 3-6 hours; (2) calcining the dried product in an air atmosphere at a temperature of 150-300° C. for 3-5 hours to obtain the hydrolysis catalyst; Wherein, the heating rate of the calcination temperature is 3-5°C / min.
9. Use of a hydrolysis catalyst as claimed in any one of claims 1 to 4, characterized in that: The hydrolysis catalyst is used to remove organic sulfur from oxygen-containing combustible gas at medium and low temperatures; Preferably, the type of organic sulfur includes carbonyl sulfide; Preferably, the volume content of oxygen in the oxygen-containing combustible gas is 0-3%, excluding 0; Preferably, the medium-low temperature is 80-160°C.
10. The use according to claim 9, characterized in that: During the process of removing organic sulfur with the hydrolysis catalyst, the space velocity is 6000-1000h -1 ; Preferably, the concentration of organic sulfur in the oxygen-containing combustible gas is 5-2000 mg / m 3 .
